BRAF V600E mutation and MET amplification as resistance pathways of the second-generation anaplastic lymphoma kinase (ALK) inhibitor alectinib in lung cancer. (August 2020) - Shi, Ruoshi; Filho, Sebastiao N. Martins; Li, Ming; Fares, Aline; Weiss, Jessica; Pham, Nhu-An; Ludkovski, Olga; Raghavan, Vibha; Li, Quan; Ravi, Deepti; Cabanero, Michael; Moghal, Nadeem; et al.
Highlights: We derived 2 post-alectinib progressed ALK + patient-derived xenograft (PDX) models. We identified MET amplification and unreported BRAFV600E as resistance mechanisms. Anti-MET/BRAF therapies combined with ALK TKI overcame resistance in the PDXs. Combination therapy against these targets may also be effective in the clinical setting. Abstract: Background: Anaplastic lymphoma kinase (ALK) targeted therapies have demonstrated remarkable efficacy in ALK-positive lung adenocarcinomas. However, patients inevitably develop resistance to such therapies. To investigate novel mechanisms of resistance to second generation ALK inhibitors, we characterized and modeled ALK inhibitor resistance of ALK-positive patient-derived xenograft (PDX) models established from advanced-stage lung adenocarcinoma patients who have progressed on one or more ALK inhibitors. Methods: Whole exome sequencing was performed to identify resistance mechanisms to ALK inhibitors in PDXs generated from biopsies at the time of relapse. ALK fusion status was confirmed using fluorescent in situ hybridization, immunohistochemistry, RNA-sequencing, RT-qPCR and western blot. Targeted therapies to overcome acquired resistance were then tested on the PDX models. Results: Three PDX models were successfully established from biopsies of two patients who had progressed on crizotinib and/or alectinib. The PDX models recapitulated the histology and ALK status of their patient tumors, as well as their matched patients' clinical treatment outcome to ALK inhibitors. Whole exome sequencing identified MET amplification and previously unreported BRAF V600E mutation as independent mechanisms of resistance to alectinib. Importantly, PDX treatment of inhibitors specific for these targets combined with ALK inhibitor overcame resistance. Conclusions: Bypass signaling pathway through c-MET and BRAF are independent mechanisms of resistance to alectinib. Individualized intervention against these resistance pathways could be viable therapeutic options in alectinib-refractory lung adenocarcinoma.